Evaluating and comparing success rates for inpatient treatment of alcohol addiction in the Czech Republic - Skorkovský, Tomáš; Vevera, Jan; Beniš, Milan; Miovský, Michal; Popov, Petr (Central European journal of public health, 2023)
OBJECTIVES: This systematic review seeks to present and compare data from studies evaluating the success of medium-term inpatient treatment of alcohol-dependent patients in the Czech Republic. Another aim was to identify the problems that make such comparisons difficult. No previous review comparing the efficiency of various therapeutic programmes has been published in the Czech Republic. METHODS: Bibliographia medica Čechoslovaca and PubMed were used to find studies published in professional medical journals since 1970 evaluating the abstinence of patients who voluntarily completed medium-term inpatient treatment of alcohol dependence. RESULTS: Medium-term inpatient treatment of alcohol addiction leads to one year of abstinence in 34% to 76% of patients. Such variance in value is largely caused by selection bias, differences in the definition of abstinence, and differences in data collection methods. CONCLUSION: The comparison of studies presented many challenges. Further steps should be taken to help compare treatment programmes in the future, as the programmes provide different therapeutic interventions of different intensities and lengths to different patients. Adequate demographic and other pretreatment characteristics data collection, detailed descriptions of therapeutic interventions, and identification of effective components of the therapeutic programme could support further research in this area, optimize existing programmes, and increase the overall treatment efficiency.
Keywords: Česká republika; hospitalizace; Ethanol; Inpatients; Czech Republic; hospitalizovaní pacienti; Alcoholism; lidé; Humans; ethanol; alkoholismus; Hospitalization